Invisible Hands, Visible Screens: Domestic Labor, Cultural Narratives, and Legal Realities in Contemporary South Korea - Siem Evelyn, Yang En; Putra, I Nyoman Darma; Arjawa, I Gusti Putu Bagus Suka; Lestari, Denok; Ambarsari, Ningrum; Resen, Putu Titah Kawitri (Udayana Journal of Law and Culture; Vol 9 No 2 (2025), 2025)
Domestic labor in South Korea, a sector historically undervalued and predominantly feminized, exists at a complex intersection of law and culture. This paper investigates the socio-legal conditions of domestic workers by examining their life experiences, their portrayal in influential South Korean cinema, and the evolving legal frameworks governing their employment. This paper further analyzes three seminal films—Kim Ki-young's The Housemaid (1960), Im Sang-soo’s The Housemaid (2010) remake, and Bong Joon-ho's Parasite (2019)—as cultural texts that reflect, reinforce, and occasionally critique societal perceptions of domestic labor, class, and gender, which in turn inform and are informed by the legal landscape. Through qualitative case studies of three Korean women domestic workers (OKN, LEY, and YEO), the research highlights the tangible impacts of legal invisibility and cultural biases on their working lives, characterized by precarity, inadequate protection, and struggles for dignity. This study scrutinizes South Korea’s Labor Standards Act, from which domestic workers have been historically excluded, and evaluates the recent Act on the Employment Improvement of Domestic Workers (2021) for its potential and limitations in addressing systemic inequities. By employing a multidisciplinary approach that integrates socio-legal analysis, feminist theory, and media studies, this research argues that cinematic narratives serve as crucial cultural mirrors, revealing societal contradictions that are deeply embedded in the legal treatment of domestic workers, thereby underscoring the urgent need for more comprehensive legal reforms and cultural shifts towards recognizing the value of domestic labor.